Catholicism, race and empire : eugenics in Portugal, 1900-1950 - Cleminson, Richard (CEU press studies in the history of medicine, 2014)
This monograph places the science and ideology of eugenics in early twentieth-century Portugal within the context of the development of eugenics in other countries in the same period. The author argues that three factors governed the impact of eugenics in Portugal: a low level of institutionalization, opposition from Catholics and the conservative nature of the Salazar regime. In Portugal eugenic science was confined to three expressions: individualized studies on mental health, often from a 'biotypological' perspective; a particular stance on racial miscegenation in the context of the substan.